2010
DOI: 10.1111/j.1749-6632.2010.05766.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of bisphosphonates in cancer treatment

Abstract: Bone metastases result in considerable morbidity and exert complex demands on health care resources. Additionally, for many patients, metastatic bone disease is a chronic condition affecting quality of life and independence over years rather than months. The bisphosphonates, notably zoledronic acid, have been shown to reduce skeletal morbidity in multiple myeloma, as well as a wide range of solid tumors affecting bone, by 30-50%. Quite appropriately, the bisphosphonates are increasingly used alongside anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 82 publications
1
43
0
2
Order By: Relevance
“…Aminobisphosphonates (i.e. zoledronic acid and risedronate) are powerful inhibitors of osteoclast activity and thereby are the standard of care in patients with diseases associated with excessive bone resorption, such as osteoporosis, multiple myeloma, and bone metastases (71). Here, we showed that zoledronic acid inhibited up-regulation of LPA 1 in bones of ovariectomized mice, confirming that modulation of LPA 1 expression was linked to mature osteoclast activity.…”
Section: Discussionsupporting
confidence: 62%
“…Aminobisphosphonates (i.e. zoledronic acid and risedronate) are powerful inhibitors of osteoclast activity and thereby are the standard of care in patients with diseases associated with excessive bone resorption, such as osteoporosis, multiple myeloma, and bone metastases (71). Here, we showed that zoledronic acid inhibited up-regulation of LPA 1 in bones of ovariectomized mice, confirming that modulation of LPA 1 expression was linked to mature osteoclast activity.…”
Section: Discussionsupporting
confidence: 62%
“…15 In other preclinical studies, it has been demonstrated that the second-generation BPs (zoledronic acid) can inhibit angiogenesis, invasion and adhesion of tumor cells, and overall tumor progression, and emerging evidence suggests that the use of these agents may block the development of bone metastases. 13 In clinical studies of patients with cancer bone metastasis, serum levels of vascular endothelial grouth factor (VEGF), an vital factor for angiogenesis, were significantly reduced in patients receiving zoledronic acid, suggesting that zoledronic acid may have a property of inhibiting angiogenesis. 27,34,35 Now, third-generation BPs (risedronate [RIS]) are available, and they are believed to be more effective and result in less toxicity.…”
Section: Targeted Delivery For Preventing and Treating Cancer Bone Mementioning
confidence: 99%
“…10,11 The drugs delivered for bone diseases include traditionally used drugs such as antibiotics and chemotherapeutics, and gene therapy reagents like plasmid deoxyribonucleic acid (DNA) or small interfering ribonucleic acid (siRNA). Currently, targeted delivery is mainly achieved by using special drugs called bisphosphonates (BPs), which have been used for treating bone diseases; [12][13][14][15][16] they are also bone affinity agents that are grafted onto NPs for the specific delivery of other drugs to bone tissues. 17 Although there is no nanodelivered treatment available in clinic so far, better designed NPs with safe (low or no toxicity) and multifunctional properties will offer specificity for the treatment of bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…4, 2018; 3 Nitrogen-containing bisphosphonates (N-BPs) are the standard treatment for osteoporosis and several other bone diseases 11,12 . Certain N-BPs (pamidronate (Aredia®), zoledronate (Zometa®)) are also routinely prescribed to prevent skeletal complications in patients with multiple myeloma and with bone metastases from other malignancies, including breast and prostate cancer 13 . However, because N-BPs cause rare yet serious side-effects, such as atypical fractures and osteonecrosis of the jaw, many patients avoid taking them [5][6][7]11 , causing the number of prescriptions to plummet over 50% in the last decade 7,14 .…”
mentioning
confidence: 99%